2022
DOI: 10.1002/smll.202107840
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Self‐Wetting Driven Monatomization of Ag Nanoparticle for Excellent Photocatalytic Hydrogen Evolution

Abstract: Metal nanoparticles (NPs) with <10 nm have demonstrated many novel applications including surprisingly low melting point, astonishing liquidlike pseudoelasticity, and outstanding hydrogen evolution performance. Here, a nanoscale self-wetting driven monatomization of Ag NPs with <5 nm on carbon nitride (CN) to fabricate Ag single-atom catalyst (Ag 1 /CN SAC) is demonstrated, and a thermodynamic approach to elucidate Ag NPs decomposing into single atoms is established. Dynamic dispersion process of Ag NPs into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…[381][382][383][384] An unconventional metal precursor was used by Yan et al in a top-down synthetic strategy towards Ag single-atoms. 385 In particular, 5 nm of Ag NPs were mixed with CN in an aqueous suspension. After calcination at 350 1C, the authors observed that most metallic nanoparticles were broken down into individual atoms, i.e.…”
Section: Wet Impregnationmentioning
confidence: 99%
“…[381][382][383][384] An unconventional metal precursor was used by Yan et al in a top-down synthetic strategy towards Ag single-atoms. 385 In particular, 5 nm of Ag NPs were mixed with CN in an aqueous suspension. After calcination at 350 1C, the authors observed that most metallic nanoparticles were broken down into individual atoms, i.e.…”
Section: Wet Impregnationmentioning
confidence: 99%
“…Yan et al annealed the prepared Ag NPs@CN at 300 °C to convert Ag NPs into Ag SAs spontaneously. [ 90 ] Figure a recorded the nanoscale self‐wetting spontaneous atomic dispersion of Ag NPs on CN. The thermodynamics and dynamics of the process were simulated and calculated by MD and DFT (Figure 2b–d).…”
Section: Design Preparation and Characterization Of Single‐atom Photo...mentioning
confidence: 99%
“…Reproduced with permission. [ 90 ] Copyright 2022, Wiley‐VCH. e) The evolution of PdNP to PdPNP and PdPSA.…”
Section: Design Preparation and Characterization Of Single‐atom Photo...mentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Charge separation, transportation and optical performance are essential to the potential of semiconductors in HER applications. [7][8][9] Nevertheless, the lack of active sites with suitable adsorption energy, the rapid recombination of photogenerated charge carriers and the low utilization ratio of visible light are obstacles to the practical application of semiconductor photocatalysts in photocatalytic H 2 generation. 10,11 Modication with cocatalysts, such as noble metals, 12 metal oxides, 13,14 metal suldes, 15,16 metal compounds [17][18][19] and metal-free compounds, 20,21 has been considered as a rational way to improve the photocatalytic activity by providing effective active sites for favorable proton adsorption and hydrogen desorption, along with assistance in electron transfer and inhibition of the rapid charge recombination.…”
Section: Introductionmentioning
confidence: 99%